Phytochemical Composition and In Vitro Antibacterial Activities of Millettia Chrysophylla and Millettia Zechiana (Journal of Science and Technology, 2022)
Millettia chrysophylla (MC) and Millettia zechiana (MZ) are two medicinal plants distributed in Africa. MZ is used traditionally to treat infectious diseases. Current literature survey suggests no scientific studies on MC and phytochemical studies on MZ were scanty with no biological activities.  In vitro antibacterial activities of the ethanol extracts of the leaves (L), stems (S), and roots (R) for both plants, and flowers (F) and twigs (T) for MZ were tested against eight laboratory bacteria strains and 28 clinical isolates of Methicillin-Resistant Staphylococcus aureus (MRSA). The chemical profile of the extracts was obtained by Gas Chromatography Mass Spectrometry (GCMS) whiles characterisation of the alkaloid, flavonoid, and tannin contents were also determined. MCS extract showed a strong and broad activity against S. epidermidis (8.79 μg/mL), E. coli (3.9 μg/mL), S. enteritidis (5.11 μg/mL) and B. cereus (5.33 μg/mL).  Broad bactericidal activity against MRSA strains: MR21, MR4 and MR19 with respective IC50 values of 72.30, 86.45 and 97.76 µg/mL were showed by MCL extract. The major components identified from the GCMS analysis included 17-octadecenoic acid (39.46%), 17-octadecynoic acid (27.90%) n-decanoic acid (27.88%), (Z, Z)-9,12-octadecadienoic acid (27.02%), (Z)-18-octadec-9-enolide (24.46%), and n-hexadecanoic acid (20.87%). MCL indicated 6.97±0.62 mg CA/g, 3.75 ± 0.12 mg TA/g, and 3.58 ± 0.18 mg RU/g for the respective contents of alkaloids, tannins, and flavonoids. These findings have given insights into the phytochemicals of M. chrysophylla and the antibacterial activities of leaves, stems and roots of M. chrysophylla and the twigs of M. zechiana for further drug discovery research.